Landscape diversity of the forest-steppe in the Tyumen Oblast (Russia) - Marshinin, A.V. (Fundamental and Experimental Biology, 2021)
Forest-steppe landscapes are ecotonic systems that are characterized by a high degree of diversity due to the combination of zonal forest and steppe landscapes, as well as swamps and meadows. The research is based on a comprehensive analysis of literary sources, topographic and thematic maps, satellite images, as well as field expeditions of 1997–2020. In the south-western part of the Tyumen Oblast, 12 types of terrain are differentiated on an area of 30,000 km2, including types of terrain of divides, ridges, flat ridges, flat depressions, hill-ock depressions, terraces, slopes, lakes and swamps, reed swamps, ravines and girders, floodplains of large rivers, small valleys. The main features of the spatial organization of landscapes in the region and the land-scape structure at the level of components are characterized. In the conditions of the region, the main part of landscapes is convenient for economic development and used in various sectors of the economy. Meadow and steppe landscapes, and partly forests are plowed. Pastures and hayfields are widespread on the territory. Such economic activities as sand and peat extraction, wood harvesting, recreational nature use, as well as fishing, hunting, and gathering have been developed. Some landscapes are protected by state as nature reserves.